Subjetivação e escolarização de um aluno surdo usuário de implante coclear: um estudo de caso fundamentado na perspectiva histórico-cultural - BARCA, Ana Paula de Araújo (Universidade Federal do Pará, 2017)
The present dissertation investigates the processes of subjectivation and schooling of a deaf student using a cochlear implant. It is a case study in a qualitative perspective of a historicalcultural perspective, inspired by the central ideas of Vygotsky and some of his commentators. In this theoretical-methodological perspective, the human being is constituted as subject by the internalization of human culture, mediated by the signs. It is understood that the school plays an important role in the process of subjectivation of the people who participate in it, for the possibility of being a space of dialogical interactions and sharing of culture. Thus, the main objective of the study was to examine the existing links between the processes of subjectivation and schooling of a deaf child using a cochlear implant, enrolled in 2016, in the second year of primary education at a school in the municipal public system of Belém -Pará. The study was divided into two distinct stages. In the first moment of the research, the historical-cultural context of the child's life was characterized. At this stage, information was collected through interviews with the child's mother, the teacher, the coordinator of the bilingual program of the Reference Center for Educational Inclusion Gabriel Lima Mendes, and the coordinator of the hospital's cochlear implant program Where the implant surgery occurred. In the second moment, we investigated the elements that make up the educational process experienced by the boy, as well as the dialogical interactions between him and the classmates. At this stage, the information about the educational process was collected through interviews and the data were organized into three categories, namely: the organization of the pedagogical work, the performance of the boy, the performance of the teacher and a trainee of the pedagogy course that accompanied the Boy in the accomplishments of his school activities. Information on dialogic interactions was collected through video records and analyzed according to the principles of microgenetic analysis of the historical-cultural matrix. The results indicated that the child underwent surgery to place the cochlear implant at two years and nine months of age. He currently attends the third year of elementary school and coexists predominantly with listeners. He has not yet made significant advances in orality and has been learning Brazilian Sign Language (BSL) since 2016. The analysis at the school level has shown that the educational process organized for him requires adaptations to be compatible with his specifics and needs. Although he has not yet acquired a language to communicate fully, in analyzing the interactions between the boy and his colleagues, there is evidence of formation of his higher psychological functions, his conscience and personality, which can be proven by means of the analysis of the process of production of meanings by the child. The study suggests possible adaptations so that the educational process lived by the boy and other implanted deaf children is a promoter of development possibilities.